A method for cleaving and transferring a two-dimensional material
Patent Information
- Application Number
- CN202311150854.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-09-07
AI Technical Summary
然而,该方法解理出的样品不适合用于测量二维材料的电学性质
[0034]本发明提供了一种普遍适用的二维材料解理方法,特别适用于解理能高的二维材料,可以制备更丰富种类的异质结。该方法利用有机材料高粘附性的特点,通过调节不同温度下有机物的状态来实现机械解理二维材料。相比于直接解理法,该方法能够解理较难解理的二维材料。与氧化铝辅助方法相比,本发明方法不会引起化学掺杂。与金辅助解理方法相比,该方法几乎不受材料本身化学性质的影响,可以用于多种不同的物理性质的研究,避免金辅助解理方法无法用于电学输运性质研究的问题。同时,解理过程在低温下进行,此时,有机材料维持一个非常硬质高粘性的状态,可以给二维材料提供一个很好的硬质支撑,避免目标样品出现褶皱或碎裂,因此可以解理得到更大更薄的二维材料。另外,该方法可以将解理好的二维材料定向转移到目标衬底上,避免传统机械解理方法获得的二维材料转移流程复杂的问题。
Smart Images

Figure CN117185287B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of two-dimensional materials science and technology, and specifically relates to a method for cleavage transfer in two-dimensional materials. Background Technology
[0002] Starting with graphene, an increasing number of two-dimensional materials have been discovered, including but not limited to transition metal dichalcogenides, oxides, and nitrides. These materials possess unique properties and broad application prospects, leading the current advancements in scientific research. In particular, when the thickness of these materials is reduced to below 10 nm, novel quantum effects emerge due to the confinement of one dimension. Because of their controllable structure and unique physical properties, two-dimensional materials and their heterostructures can serve as excellent carriers for the storage and manipulation of spin and qubits. Therefore, in-depth research on two-dimensional materials will drive the development of fields such as spintronics and quantum computing.
[0003] There are generally two methods for preparing thin-layer two-dimensional materials in existing technologies: top-down and bottom-up methods. The former refers to separating a thin layer from a thick material, while the latter refers to directly growing a thin-layer sample. Top-down methods include mechanical exfoliation, liquid-phase exfoliation, and ion exchange methods; while bottom-up methods include chemical vapor deposition and hydrothermal methods. Except for mechanical exfoliation, other methods may introduce various impurities, resulting in relatively poor quality thin-layer samples. Therefore, when studying the physical properties of two-dimensional materials, mechanical exfoliation is usually used to obtain high-quality thin-layer samples.
[0004] However, due to differences in crystal structure, different two-dimensional materials exhibit variations in in-plane and out-of-plane binding energies, resulting in different cleavage energies. Currently, various mechanical cleavage methods have been developed, including ordinary mechanical cleavage, alumina-assisted cleavage, and gold-assisted cleavage.
[0005] The conventional mechanical cleavage method, discovered in 2004, involves peeling a thick layer of two-dimensional material using adhesive tape and attaching it to the surface of a silicon wafer. After the tape is removed, a small portion of the two-dimensional material remains on the wafer surface, including thin samples. This method is generally suitable for easily cleavable two-dimensional materials, such as graphene.
[0006] Alumina-assisted cleavage is an emerging method discovered in 2017. This method involves depositing a layer of alumina onto the surface of a two-dimensional material, which acts as an adhesive and support, allowing difficult-to-cleave samples (such as iron, germanium, and tellurium) to be cleaved into thinner, larger two-dimensional layers. However, the procedure is relatively complex, and the surface deposition may affect the physicochemical properties of the sample.
[0007] Gold-assisted cleavage, discovered in 2018, involves depositing gold onto a silicon wafer and then attaching the sample to the gold layer. Two-dimensional materials with phosphorus chalcogenides as their outermost layer have a strong affinity for gold; therefore, for such materials, gold-assisted cleavage can dissociate large-area, thin-layer samples. However, the samples cleaved using this method are not suitable for measuring the electrical properties of two-dimensional materials.
[0008] In addition, there are some existing technologies that utilize the viscoelasticity of PDMS gel to cleave two-dimensional materials. However, during the use of PDMS gel, the adhesion between PDMS and the two-dimensional material is not very uniform because the two-dimensional material sheet on the tape itself has undulations. Furthermore, since PDMS gel is in a gel state, a large number of wrinkles and fragments will occur in the sample during the cleavage process, making it impossible to form thinner and larger two-dimensional samples. In addition, the viscoelasticity of PDMS gel is generally applicable to graphene and some transition metal dichalcogenides, but not to materials that are difficult to cleave. Summary of the Invention
[0009] Therefore, the technical problem to be solved by the present invention is to overcome the above-mentioned defects in the cleavage transfer process of two-dimensional materials in the prior art, thereby providing a method for cleavage transfer of two-dimensional materials.
[0010] Therefore, the present invention provides the following technical solution:
[0011] This invention provides a method for cleavage transfer in two-dimensional materials, comprising the following steps:
[0012] S1, use adhesive tape to peel off a sheet of two-dimensional material from the surface of the two-dimensional material to form a master tape;
[0013] S2, applying organic material to the master tape at a melting or softening temperature to impregnate the two-dimensional material sheet; wherein, the organic material has the characteristics of melting or softening at 50-120°C, curing at 20-25°C, and being viscous; preferably, it has high viscous properties;
[0014] S3, cool down to 20-25℃, tear off the mother tape, and obtain a sheet with the target sample;
[0015] S4, Align the sheet with the target sample with the target substrate, heat it to the temperature at which the organic material melts or softens, so that the target sample is attached to the target substrate, and cool it down to 20-25℃;
[0016] S5 uses organic solvents to clean the organic materials, thus completing the transfer.
[0017] In this invention, the organic material is an organic substance that softens or melts with increasing temperature, or an organic substance that solidifies with decreasing temperature. Optionally, the organic material includes, but is not limited to, at least one of paraffin wax, petroleum-derived binder wax 509 (Crystalbond 509), polymethyl methacrylate (PMMA), and polyethylene terephthalate (PET).
[0018] In this invention, the cooling temperature range in step S4 is determined by the properties of the organic material, ensuring that the organic material is in a rigid state. In this state, the two-dimensional material is tightly adhered to the rigid organic material. Adhesive tape is repeatedly applied to the surface of the two-dimensional material and then peeled off until a thinner or even single-layer two-dimensional material is obtained.
[0019] Optionally, in step S2, the organic material is first transferred to the surface of the support substrate to form an organic material layer, and then applied to the master tape. This mainly utilizes the smooth surface of the support substrate to smooth the upper surface of the organic material, and then the master tape is applied to the smooth surface of the organic material. The organic material is softened or melted by heating, and after a certain period of time, the organic material adheres to the cleaved surface of the two-dimensional material. Then, it is cooled to solidify or solidify.
[0020] And / or, during the application process, ensure the operation is slow and avoid the formation of air bubbles.
[0021] Optionally, in step S2, the organic material is heated to a melting or softening temperature, transferred to the surface of a supporting substrate, and cooled to room temperature to form an organic material layer;
[0022] Alternatively, an organic material layer can be formed by attaching the organic material layer to the surface of the support substrate using double-sided adhesive.
[0023] Optionally, in step S1, after several applications of adhesive tape, a two-dimensional material sheet of the target size is obtained to form a master tape. If the two-dimensional material sheet on the master tape is too thick or too small, the traditional adhesive tape cleaving method can be used to cleave the two-dimensional material along the two-dimensional plane to increase the coverage area of the two-dimensional material sheet, and then it is applied to the surface of the organic material.
[0024] Optionally, in step S3, if the thickness of the target sample does not meet the requirements, adhesive tape is used to apply adhesive tape several times until the thickness of the target sample meets the requirements.
[0025] Optionally, in step S4, a two-dimensional material transfer stage is used for the operation.
[0026] Optionally, in step S4, the shape, size, and position of the sample are determined using a microscope. Then, the cleaved sample is transferred to the target substrate on a two-dimensional material transfer stage. The target substrate can be any location where the sample is to be placed; it can be a silicon wafer, a silicon wafer with electrodes, mica, or a solid ion-conducting substrate. During the transfer process, the sample needs to be brought close to the target substrate and then slowly heated to a softening or melting temperature. During the heating process, the organic material and the target sample will slowly adhere to the target substrate, and there will be no organic matter between the sample and the substrate.
[0027] Specifically, step S4 includes the following steps: placing the sheet with the target sample on the cantilever end of the two-dimensional material transfer stage, placing the target substrate on the fixed end of the two-dimensional material transfer stage, observing through a microscope on the two-dimensional material transfer stage, moving the cantilever end to align the sheet with the target sample and the target substrate, heating the target substrate to 40-60°C, adjusting the two-dimensional material transfer stage to shorten the distance between the target sample and the target substrate until they touch. After touching, the contact interface will slowly spread out from a point. Once the target sample is completely attached to the target substrate, adjust the two-dimensional material transfer stage to heat the target substrate to 60-80°C to adhere the target sample to the target substrate until the contact interface no longer moves, and then cool to room temperature (20-25°C).
[0028] Optionally, the supporting substrate is at least one of glass sheet, quartz sheet or mica;
[0029] And / or, the target substrate is one of silicon oxide, aluminum oxide, silicon nitride, ferroelectric substrate, magnetic substrate, piezoelectric ceramic, and ion conductor;
[0030] And / or, the organic solvent includes at least one of acetone, isopropanol, chloroform, tetrahydrofuran, anisole, alcohol, and soapy water.
[0031] Optionally, the two-dimensional material is one of graphene, III-V semiconductor materials, black phosphorus, transition metal dichalcogenides, iron-based superconducting materials, three-dimensional topological insulator materials, magnetic topological insulator materials, two-dimensional magnetic materials, or quasi-one-dimensional crystal materials (molybdenum trioxide, bismuth bromide).
[0032] Typically, without limitation, group III-V semiconductor materials can be gallium telluride; transition metal dichalcogenides can be molybdenum disulfide; iron-based superconducting materials can be iron selenide or iron selenide telluride; three-dimensional topological insulator materials can be bismuth tris(selenide, telluride); magnetic topological insulator materials can be manganese bismuth telluride; and two-dimensional magnetic materials can be chromium germanium telluride.
[0033] The technical solution of this invention has the following advantages:
[0034] This invention provides a universally applicable method for cleaving two-dimensional materials, particularly suitable for two-dimensional materials with high cleavage energy, enabling the fabrication of a wider variety of heterostructures. This method utilizes the high adhesiveness of organic materials, achieving mechanical cleavage of two-dimensional materials by adjusting the state of the organic material at different temperatures. Compared to direct cleavage methods, this method can cleave even more difficult-to-cleave two-dimensional materials. Compared to alumina-assisted methods, this method does not induce chemical doping. Compared to gold-assisted cleavage methods, this method is almost unaffected by the chemical properties of the material itself, allowing for the study of various physical properties and avoiding the limitation of gold-assisted cleavage methods in studying electrical transport properties. Furthermore, the cleavage process is carried out at low temperatures, where the organic material maintains a very hard and highly viscous state, providing excellent rigid support for the two-dimensional material and preventing wrinkles or fragmentation of the target sample. Therefore, larger and thinner two-dimensional materials can be cleaved. In addition, this method can directionally transfer the cleaved two-dimensional material onto a target substrate, avoiding the complex transfer process of traditional mechanical cleavage methods. Attached Figure Description
[0035] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0036] Figure 1 This is a schematic diagram of the two-dimensional material cleavage transfer method in Embodiment 1 of the present invention;
[0037] Figure 2 These are photographs of the target samples (a is graphite, b is molybdenum disulfide) after transfer in Example 1 of the present invention;
[0038] Figure 3 These are photographs of the samples before (a) and after (b) transfer in Embodiment 2 of the present invention;
[0039] Figure 4 These are photographs of the samples before (a) and after (b) transfer in Embodiment 3 of the present invention;
[0040] Figure 5 These are photographs of the samples before (a) and after (b) transfer in Comparative Example 1 of this invention;
[0041] Figure label:
[0042] 101. Two-dimensional material sheet; 102. Adhesive tape; 103. Glass sheet; 104. Organic material; 105. Target substrate. Detailed Implementation
[0043] The following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.
[0044] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.
[0045] Example 1
[0046] This embodiment provides a cleavage transfer method for two-dimensional materials, and the cleavage transfer flowchart is shown below. Figure 1 As shown, the organic material used in this example is Crystalbond 509, a petroleum extract commonly used for sample fixation. The cleavage material is graphene, a relatively easy-to-cleave two-dimensional material. The specific steps are as follows:
[0047] Step 1: Prepare two-dimensional material master tape
[0048] A small piece of graphite crystal is torn onto the tape using adhesive tape. Through repeated cleaving and bonding of the tape, the graphite crystal on the tape becomes relatively thin (generally less than 1 μm). This is called the master tape.
[0049] Step 2: High-temperature adhesion
[0050] Crystalbond 509 is melted onto a glass slide and then cooled to create a smooth spherical or flat surface away from the glass slide. The master tape containing graphite crystals is then heated to 60°C, and the glass slide is moved up and down to slowly bring the Crystalbond 509 from the slide closer to the master tape. Once the Crystalbond 509 adheres to the master tape, it melts slowly upon heating, wetting the crystals on the master tape. This process must be slow to avoid the formation of air bubbles.
[0051] Step 3: Cooling and solidification
[0052] Once Crystalbond 509 and the master tape have adhered to a sufficiently large area, the temperature is lowered to room temperature, allowing Crystalbond 509 to solidify.
[0053] Step 4: Cleavage the sample
[0054] After cooling, Crystalbond 509 solidifies. Gently peel the master tape slowly from Crystalbond 509. At this point, some graphite crystals, including some thin layers, will adhere to Crystalbond 509. Observe the sample under a microscope. If a relatively thin sample is found, proceed to the next step. If not, use a clean piece of tape to reapply to the Crystalbond 509 with crystals, pressing the tape to ensure a firm adhesion between the tape and the crystals. Then peel off the tape, removing some graphite crystals to thin the remaining crystals on Crystalbond 509. Check under a stereomicroscope for crystals of a satisfactory thickness (generally 0.3-100 nm). If found, proceed to the next step; otherwise, continue using tape to thin the crystals.
[0055] Step 5: High-temperature transfer
[0056] A glass slide with the target thin-layer sample and Crystalbond 509 are placed on the cantilever end of a two-dimensional material transfer stage, while the target substrate is placed on the fixed end. Observation is performed using a microscope on the two-dimensional material transfer stage. The cantilever end is moved to align the target thin-layer sample with the substrate to be transferred (in this embodiment, the substrate is a silicon wafer with a 285nm SiO2 layer, hereinafter the same). The substrate is slowly heated to 50°C, and the transfer stage is adjusted to gradually shorten the distance between the thin-layer sample and the substrate until they touch. After touching, the contact interface slowly spreads out from a single point. Once the entire thin-layer sample is attached to the substrate, the substrate temperature is heated to 60°C to accelerate the melting of Crystalbond 509 until the contact interface stops moving. The substrate is then cooled to room temperature.
[0057] Step 6: Cleaning organic matter
[0058] The glass slide, Crystalbond 509, and the substrate containing the sample are placed together in an acetone solution, which melts the Crystalbond 509. The thin sample detaches from the glass slide on the target substrate. The target substrate containing the sample is then rinsed with acetone and isopropanol in sequence. After rinsing, it is dried, and the transfer process is complete.
[0059] The above steps can be repeated by replacing the graphite crystal with molybdenum disulfide crystal to cleave molybdenum disulfide.
[0060] This method can tear thinner and larger crystals than ordinary mechanical cleavage methods. See [link to relevant documentation]. Figure 2 Figure a shows a three-layer graphene sample, and Figure b shows a thin-layer molybdenum disulfide sample. Figure 2The dimension scale in the figure is 50 micrometers. As can be seen from the figure, the samples (purple and blue in the figure are thin-layer samples) are uniform and flat, with a large area. Judging from the color, they are basically samples with 5 layers or less (samples of different thicknesses have different colors on silicon wafers with 285nm oxide layers. Initially, the sample thickness was measured by atomic force microscopy (AFM). The sample thickness was divided by the theoretical thickness of a single sample to obtain the number of layers. Then, the sample color and the number of layers were correlated to form empirical data. Based on the empirical data, the sample thickness can be judged by color. The same applies below).
[0061] Example 2
[0062] This embodiment provides a cleavage transfer method for two-dimensional materials. The organic material used is Crystalbond 509, a petroleum extract commonly used for sample fixation. The two-dimensional material to be cleaved is MnBi2Te4, a relatively difficult-to-cleave two-dimensional material. The specific steps are as follows:
[0063] Step 1: Prepare two-dimensional material master tape
[0064] A small piece of MnBi2Te4 crystal is torn onto the tape using adhesive tape. Through repeated cleaving and bonding of the tape, the thickness of the MnBi2Te4 crystal on the tape is reduced to less than 1 μm. This is called the master tape.
[0065] Step 2: High-temperature adhesion
[0066] Crystalbond 509 is melted onto a glass slide, then cooled to create a smooth spherical or flat surface away from the glass slide. A master tape containing MnBi₂Te₄ crystals is then heated to 60°C. The glass slide is moved up and down, allowing the Crystalbond 509 on the slide to slowly approach the master tape. Once the Crystalbond 509 adheres to the master tape, it melts slowly upon heating, wetting the crystals on the master tape. This process is carefully controlled to avoid the formation of air bubbles.
[0067] Step 3: Cooling and solidification
[0068] Once Crystalbond 509 and the master tape have adhered to a sufficiently large area, the temperature is lowered to room temperature, allowing Crystalbond 509 to solidify.
[0069] Step 4: Cleavage the sample
[0070] After cooling, Crystalbond 509 solidifies. Gently peel the master tape slowly from Crystalbond 509. At this point, some MnBi2Te4 crystals will adhere to Crystalbond 509, including some thin layers. Observe the sample under a microscope. If a relatively thin sample is found, proceed to the next step. If not, use a clean piece of tape to reapply to the Crystalbond 509 with crystals already present. Press the tape to ensure a firm adhesion between the tape and the crystals, then peel it off. Some MnBi2Te4 crystals will adhere, thinning the remaining crystals on Crystalbond 509. Check under a stereomicroscope for crystals around 10 nm in size. If found, proceed to the next step; otherwise, continue using tape to thin the crystals.
[0071] Step 5: High-temperature transfer
[0072] A glass slide with the target thin-layer sample and Crystalbond 509 are placed on the cantilever end of a 2D material transfer stage, while the target substrate is placed on the fixed end. Observation is performed using a microscope on the stage. The cantilever end is moved to align the target thin-layer sample with the substrate. The substrate is slowly heated to 50°C. The transfer stage is adjusted to gradually shorten the distance between the thin-layer sample and the substrate until they touch. After contact, the contact interface slowly spreads out from a single point. Once the entire thin-layer sample is adhered to the substrate, the substrate temperature is increased to 60°C to accelerate the melting of Crystalbond 509 until the contact interface stops moving. The surface is then cooled to room temperature.
[0073] Step 6: Cleaning organic matter
[0074] The glass slide, Crystalbond 509, and the substrate containing the sample are placed together in an acetone solution, which melts the Crystalbond 509. The thin sample detaches from the glass slide on the target substrate. The target substrate containing the sample is then rinsed with acetone and isopropanol in sequence. After rinsing, it is dried, and the transfer process is complete.
[0075] This method can tear thinner and larger crystals than ordinary mechanical cleavage methods. See [link to relevant documentation]. Figure 3 The size scale is 20 micrometers. As can be seen from the figure, the thin-layer sample (a is a transmission image, the gray area is the thin-layer sample, the brighter the color, the thinner the area; b is a reflection image on the silicon wafer, the blue and purple in the image are thin layers, and the only bright yellow-white part is the thick layer) is uniform and wrinkle-free. The thickness of the sample varies in different areas, and the sample is within 5 van der Waals layers.
[0076] Example 3
[0077] This embodiment provides a cleavage transfer method for two-dimensional materials. The organic material used is PET (manufacturer Midwest Products, model 703-01), a petroleum extract commonly used for sample fixation. The cleavage material is FeSeTe, a relatively difficult-to-cleave two-dimensional material. The specific steps are as follows:
[0078] Step 1: Prepare two-dimensional material master tape
[0079] A small piece of FeSeTe crystal is torn onto the tape using adhesive tape. Through repeated cleaving and bonding of the tape, the thickness of the FeSeTe crystal on the tape is reduced to less than 1 micrometer. This is called the master tape.
[0080] Step 2: High-temperature adhesion
[0081] Use transparent polyimide double-sided tape to adhere the PET film to the glass slide. Then, heat the master tape containing FeSeTe crystals to 90°C, and control the up-and-down movement of the glass slide so that the PET on the slide slowly approaches the master tape. Once the PET is attached to the master tape, it slowly and slightly vitrifies upon heating, gradually adhering to the crystals on the master tape. Ensure this process is slow to avoid the formation of air bubbles.
[0082] Step 3: Cooling and solidification
[0083] Once the PET and the mother tape have adhered to a sufficiently large area, the temperature is lowered to room temperature, causing the PET to move away from its glass transition temperature and remain in a solid state.
[0084] Step 4: Cleavage the sample
[0085] After cooling, gently and slowly peel the master tape off the PET. Some FeSeTe crystals will adhere to the PET at this point, including some thin layers. Observe the sample under a microscope. If a relatively thin sample is found, proceed to the next step. Otherwise, use a clean piece of tape to reapply it to the PET with the existing crystals, pressing the tape to ensure a firm adhesion between the tape and the crystals. Then peel off the tape, removing some FeSeTe crystals to thin the remaining crystals on the PET. Check under a metallographic microscope for crystals thinner than 20 nm. If found, proceed to the next step; otherwise, continue using tape to thin the crystals.
[0086] Step 5: High-temperature transfer
[0087] A glass slide with the target thin-layer sample and PET are placed on the cantilever end of a two-dimensional material transfer stage, while the target substrate is placed on the fixed end. Observation is performed using a microscope on the stage. The cantilever end is moved to align the target thin-layer sample with the substrate. The substrate is slowly heated to 90°C. The transfer stage is adjusted to gradually shorten the distance between the thin-layer sample and the substrate until they touch. After contact, the contact interface slowly spreads out from a single point. Once the entire thin-layer sample is adhered to the substrate, the substrate temperature is increased to 120°C to accelerate the contact between the PET and the target substrate until the contact interface stops moving. Simultaneously, the high temperature reduces the adhesion of the double-sided adhesive. After removing the glass slide, the PET and sample remain on the target substrate. The substrate is then cooled to room temperature.
[0088] Step 6: Cleaning organic matter
[0089] The PET and the substrate containing the sample were placed together in a chloroform solution, which melted the PET. The thin sample detached from the glass slide on the target substrate. The target substrate containing the sample was then rinsed with acetone and isopropanol in sequence. After rinsing, it was dried, and the transfer process was completed.
[0090] This method can tear thinner and larger crystals than ordinary mechanical cleavage methods. See [link to relevant documentation]. Figure 4 The dimension scale is 20 micrometers. As can be seen from the figure, a flat thin-layer sample can be cleaved. Figure 4 (In the blue area of b), different layer thicknesses can be clearly distinguished.
[0091] Comparative Example 1
[0092] This comparative example provides a method for cleavage transfer in two-dimensional materials, the specific steps of which are as follows:
[0093] Step 1: Prepare two-dimensional material master tape
[0094] A small piece of MnBi2Te4 crystal is torn onto the tape using adhesive tape. Through repeated cleaving and bonding of the tape, the thickness of the MnBi2Te4 crystal on the tape is reduced to less than 1 μm. This is called the master tape.
[0095] Step 2: PDMS Adhesion
[0096] Apply PDMS to the tape containing MnBi2Te4 crystals, then quickly peel off the PDMS. At this point, MnBi2Te4 crystals are still attached to the PDMS.
[0097] Step 3: Transfer the sample onto the silicon substrate.
[0098] The sample on PDMS was transferred onto a silicon wafer using a two-dimensional material transfer stage. The PDMS was slowly applied to the silicon wafer, allowing the MnBi₂Te₄ crystals to adhere to it. Then, the PDMS was slowly lifted, causing the MnBi₂Te₄ crystals to fall off and remain on the silicon wafer. See sample photographs. Figure 5 The dimension scale is 20 micrometers. The image shows a yellow sample with noticeable edge undulations, indicating a very thick sample, at least 100 nm thick. This demonstrates the significant advantages of the method described in this invention.
[0099] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A method for cleavage transfer in two-dimensional materials, characterized in that, Includes the following steps: S1, use adhesive tape to peel off a sheet of two-dimensional material from the surface of the two-dimensional material to form a master tape; S2, applying organic material to the master tape at a melting or softening temperature to impregnate the two-dimensional material sheet; wherein, the organic material has the characteristics of melting or softening at 50-120°C, curing at 20-25°C, and being adhesive; the organic material includes at least one of paraffin wax and petroleum-derived adhesive wax 509. S3, cool down to 20-25℃, tear off the mother tape, and obtain a sheet with the target sample; S4, Align the sheet with the target sample with the target substrate, heat it to the temperature at which the organic material melts or softens, so that the target sample is attached to the target substrate, and cool it down to 20-25℃; S5 uses organic solvents to clean the organic materials, thus completing the transfer.
2. The two-dimensional material cleavage transfer method according to claim 1, characterized in that, In step S2, the organic material is first transferred to the surface of the support substrate to form an organic material layer, and then applied to the master tape. During the application process, air bubbles should be avoided.
3. The two-dimensional material cleavage transfer method according to claim 2, characterized in that, In step S2, the organic material is preheated to a melting or softening temperature, transferred to the surface of the support substrate, and cooled to room temperature to form an organic material layer.
4. The two-dimensional material cleavage transfer method according to claim 1, characterized in that, In step S1, after several applications of adhesive tape, a two-dimensional material sheet of the target size is obtained, forming the master tape.
5. The two-dimensional material cleavage transfer method according to claim 1, characterized in that, In step S3, if the thickness of the target sample does not meet the requirements, adhesive tape is used to apply adhesive tape several times until the thickness of the target sample meets the requirements.
6. The two-dimensional material cleavage transfer method according to claim 1, characterized in that, In step S4, a two-dimensional material transfer stage is used for the operation.
7. The two-dimensional material cleavage transfer method according to claim 6, characterized in that, Step S4 includes the following steps: placing the sheet with the target sample on the cantilever end of the two-dimensional material transfer stage, placing the target substrate on the fixed end of the two-dimensional material transfer stage, observing through a microscope on the two-dimensional material transfer stage, moving the cantilever end to align the sheet with the target sample and the target substrate, heating the target substrate to 40-60°C, adjusting the two-dimensional material transfer stage to make the sheet with the target sample contact the target substrate, heating the target substrate to 60-80°C to attach the target sample to the target substrate, and cooling to 20-25°C.
8. The two-dimensional material cleavage transfer method according to any one of claims 2-3, characterized in that, The supporting substrate is at least one of glass sheet, quartz sheet or mica.
9. The two-dimensional material cleavage transfer method according to any one of claims 3-7, characterized in that, The target substrate is one of silicon oxide, aluminum oxide, silicon nitride, ferroelectric substrate, magnetic substrate, piezoelectric ceramic, and ion conductor; And / or, the organic solvent includes at least one of acetone, isopropanol, chloroform, tetrahydrofuran, anisole, and alcohol.
10. The two-dimensional material cleavage transfer method according to claim 8, characterized in that, The two-dimensional material is one of graphene, III-V semiconductor materials, black phosphorus, transition metal dichalcogenides, iron-based superconducting materials, three-dimensional topological insulator materials, magnetic topological insulator materials, two-dimensional magnetic materials, or quasi-one-dimensional crystal materials.
Citation Information
Patent Citations
Method for transferring two-dimensional material to transmission electron microscope grating
CN114486960A
Method for accurately transferring large-area two-dimensional material
CN116605907A
